2014
DOI: 10.1590/s1517-83822014000400002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Shigella spp. and enteroinvasive Escherichia coli (EIEC) and their differentiation

Abstract: Shigellosis produces inflammatory reactions and ulceration on the intestinal epithelium followed by bloody or mucoid diarrhea. It is caused by enteroinvasive E. coli (EIEC) as well as any species of the genus Shigella, namely, S. dysenteriae, S. flexneri, S. boydii, and S. sonnei. This current species designation of Shigella does not specify genetic similarity. Shigella spp. could be easily differentiated from E. coli, but difficulties observed for the EIEC-Shigella differentiation as both show similar biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 79 publications
1
54
0
1
Order By: Relevance
“…Our study suggests that culture‐positive cases may experience a more clinically severe illness, with a greater number of symptoms and increased chance of hospitalisation than culture‐negative/PCR‐positive cases. Our finding of differences in clinical severity may be partially explained by evidence that indicates that EIEC expresses less virulence genes than Shigella 24,25 and therefore can present as a less severe clinical illness 26 . However, without further laboratory testing data on the differentiation between EIEC and Shigella for culture‐negative/ ipaH PCR‐positive cases in our study, we cannot determine whether a subset of cases in the culture‐negative group were in fact EIEC, or whether the differences in clinical severity between groups can be explained by inherent differences in the clinical presentation of shigellosis.…”
Section: Discussionmentioning
confidence: 83%
“…Our study suggests that culture‐positive cases may experience a more clinically severe illness, with a greater number of symptoms and increased chance of hospitalisation than culture‐negative/PCR‐positive cases. Our finding of differences in clinical severity may be partially explained by evidence that indicates that EIEC expresses less virulence genes than Shigella 24,25 and therefore can present as a less severe clinical illness 26 . However, without further laboratory testing data on the differentiation between EIEC and Shigella for culture‐negative/ ipaH PCR‐positive cases in our study, we cannot determine whether a subset of cases in the culture‐negative group were in fact EIEC, or whether the differences in clinical severity between groups can be explained by inherent differences in the clinical presentation of shigellosis.…”
Section: Discussionmentioning
confidence: 83%
“…Given that the ipaH gene (which is also present in Shigella spp.) is carried in a plasmid, the gene could easily be transmitted to non-pathogenic E. coli strains and other bacterial species, thus transferring the invasive characteristics to the new organisms [51,52]. In a study conducted by Sansonetti et al [53], the authors reported that loss of the invasive plasmid resulted in the loss of the virulent invasive potential in Shigella spp., while the reintroduction of the plasmid into avirulent strains led to the reestablishment of the invasive potentials.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, O antisera of EIEC and Shigella should be used 1, 441. Bacterial colonies with this characteristic can be screened for the classical EIEC serogroups O28ac, O29, O112, O124, O136, O143, O144, O152, O159, O164, O169, and O173 1, 441, 443. EIEC invasive capacity can be evaluated using the Sereny guinea pig eye test 444 and tissue culture assays, 445 which are more markedly limited to reference laboratories.…”
Section: Enteroinvasive E Colimentioning
confidence: 99%